Platelet-rich plasma therapy in the treatment of androgenic alopecia - review - Beata Getka; Kinga Przyborowska; Mateusz Rukat; Michał Łata; Justyna Kwiecień; Katarzyna Wiejak (Kazimierz Wielki University, 2024)
Hair loss is a problem that affects many people around the world. Androgenic alopecia (AGA) is the most common cause of hair loss affecting up to 50% of men and 40% of women over the age of 50. This type of hair loss is mediated by androgens, the strongest of which is dihydrotestosterone (DHT). This hormone influences the weakening hair follicles. The problem of excess DHT and the associated androgenic hair loss may concern people practicing sports, especially aerobic disciplines of moderate and high intensity. In the recent decades, many topical and oral therapies have been introduced to delay and stop hair loss. However, commonly used medications have only a partial and temporary effect, therefore alternative treatment methods are needed. Platelet-rich plasma (PRP) is known, among other things, for its use in orthopedics. The use of PRP may benefit athletes in the treatment of injuries to tendons, ligaments, muscles and cartilage. Many publications indicate good results with the use of PRP in the treatment of hair loss. The aim of this study is to summarise the published reports on the effect of platelet-rich plasma (PRP) on hair loss prevention in people with androgenic alopecia (AGA) and to analyse the papers discussing androgen levels in physically active people.